Cross-Stressful Adaptation to Drought and High Salinity Is Related to Variable Antioxidant Defense, Proline Metabolism, and Dehydrin b Expression in White Clover - Yao Ling; Duo Wang; Yan Peng; Dandan Peng; Zhou Li (Agronomy)
A previous exposure to drought priming (DP) or salt priming (SP) could significantly improve future tolerance to both the same and different abiotic stresses, which is an effective mitigation strategy for plants to adapt to changing environmental conditions. If the type of stress priming is different from subsequent abiotic stress, this indicates that plants are trained to acquire cross tolerance. The objective of this study was to explore DP-regulated cross tolerance to salt stress and SP-induced cross tolerance to drought associated with changes in growth, antioxidant defense, proline metabolism, and the expression of the dehydration-responsive gene Dehydrin b involved in the stabilization of membrane systems, cryoprotection of intracellular proteins, and enhancement in water retention capacity in white clover (Trifolium repens). Plants were pretreated by initial DP or SP and then subjected to subsequent salt stress or drought stress for 10 days, respectively. The results demonstrated that DP significantly increased number of roots during subsequent salt stress, whereas SP significantly improved stem length, root length, and number of roots under drought stress, which indicated that the SP exhibited more pronounced and positive effects on mitigating subsequent drought-induced growth retardant. Both salt stress and drought resulted in significant increases in electrolyte leakage and contents of superoxide anion, hydrogen peroxide, and malonaldehyde due to reduced superoxide dismutase, peroxide, and catalase, as well as key enzyme activities in the ascorbate–glutathione cycle. SP or DP could significantly enhance these enzyme activities to alleviate subsequent drought- or salt-induced oxidative damage. SP or DP also significantly improved the accumulation of proline contributing to better water homeostasis by promoting biosynthetic enzyme activities (Δ1-pyrroline-5-carboxylate synthetase and aminotransferase) and restricting proline dehydrogenase activity for proline degradation under drought or salt stress, respectively. In addition, SP significantly up-regulated the expression of dehydrin b under drought stress, but DP failed to induce the expression of dehydrin b in response to subsequent salt stress. The current findings proved that the pre-exposure of white clover plants to DP or SP could effectively mitigate the negative effects of subsequent salt stress or drought related to some common and different pathways. Plants pretreated by initial DP or SP exhibited better adaption to subsequent different stress by regulating growth, physiological, metabolic, and transcriptional changes.